1986
DOI: 10.1139/m86-089
|View full text |Cite
|
Sign up to set email alerts
|

Properties of urease from Ureaplasma urealyticum: kinetics, molecular weight, and demonstration of multiple enzyme isoelectric point forms

Abstract: In the several strains of Ureaplasma urealyticum that we examined, all originally isolated from human sources, the ureases were found to have a pH optimum between 7.2 and 7.5, and the Km was approximately 2.5 mM urea. Using nonreducing, nondenaturing conditions for polyacrylamide gel electrophoresis, the molecular weight of the holoenzyme was determined to be approximately 380 000. Treatment with reducing agents did not affect the electrophoretic mobility and, therefore, the molecular weight of ureaplasma urea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
2

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 27 publications
1
8
2
Order By: Relevance
“…However, multiple pIs are not an uncommon biochemical finding, particularly after electrochemical separation. Multiple enzyme isoelectric point forms in the urease of the Mollicutes U. urealyticum have been reported (Eng et al, 1986). Although our finding indicates that there are multiple forms of the AK enzyme in our preparations, this is not convincing evidence of naturally occurring isoenzymes.…”
Section: Discussioncontrasting
confidence: 66%
“…However, multiple pIs are not an uncommon biochemical finding, particularly after electrochemical separation. Multiple enzyme isoelectric point forms in the urease of the Mollicutes U. urealyticum have been reported (Eng et al, 1986). Although our finding indicates that there are multiple forms of the AK enzyme in our preparations, this is not convincing evidence of naturally occurring isoenzymes.…”
Section: Discussioncontrasting
confidence: 66%
“…In addition, this genetic variation, in particular Comparison of urease genes from serotypes 1 and 8 showed minor differences. In particular, the deduced UreB and UreC polypeptides from serotype 1 have a lower molecular weight than those of serotype 8, this finding concurring with the difference previously observed by gel electrophoresis of the ureases from these serotypes (18).…”
Section: Discussionsupporting
confidence: 90%
“…A single form was observed for Bacillus pasteur/ii and Brei'ibacteeriun t amninoia genes ureases at pl values of 4.6 and 4.1, respectively (37,167). In contrast, four bands were observed (pl, 4.3 to 4.7) for Arthlobacter oxvdans urease (204) and two or three bands (pl, 5.0 to 5.2) for the cell extracts from U. urealyticuin (47,199). In addition, analysis of cell extracts from Morganella morganii, Proteuts mnir-abilis, Protelus i'ulgaris, Proi,iclencia rettgeri, and Prol'idencia stluaIr'tii (97) revealed that each species possessed a major form of urease (pl, 5.1 to 5.9) and at least one secondary form.…”
Section: )mentioning
confidence: 92%